Assimilation of FY-4A GIIRS radiance observations in the forecast of Typhoon Bavi - Xiao, Xianjun; Lu, Qifeng; Lv, Xinyan; Shen, Wenqi (Frontiers in Earth Science, 2023)
We assimilated radiance observations from the Geostationary Interferometric Infrared Sounder (GIIRS) onboard the FengYun-4A geostationary satellite to evaluate their impact on the forecast of Typhoon Bavi. We selected 30 temperature channels, representing 90% of the information content of all the temperature channels, for assimilation based on the Shannon entropy method. All the radiance observations above the cloud-top were assimilated by comparing the channel height with the cloud-top height coming from the product of the Advanced Geosynchronous Radiation Imager(AGRI). The assimilation of the GIIRS observations decreased the root-mean-square error of the temperature by 2% and improved the precipitation forecast. The rain band in southeast China was reproduced well, which showed that infrared hyperspectral radiance observations have great value in improving the circulation around typhoons and therefore give better forecasts.